DINAMIKA PESANTREN KONTEMPORER - Syamsul Ma’arif (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2011)
This article will explain about the contemporary developments in the pesantren (Islamic boarding schools), especially its role in maintaining the tradition and stem infiltration of religious radicalism at the pesantren. The steps that can be used by pesantren is by teaching inclusive faith and the reformulation of multicultural curriculum for the students (santri). All this, with consideration for each movement by fundamentalists and extremists who cast a